Kitar Pembiakan Anadara Granosa (Bivalvia: Arcidae) Di Banda Aceh, Lhokseumawe (Indonesia) Dan Pulau Pinang (Malaysia) - Khalil, Munawar (2013)
A study on reproductive cycle of blood cockle Anadara granosa (Linnaeus, 1758) (Bivalvia : Arcidae) was conducted at three different muddy areas namely Banda Aceh (Indonesia), Lhokseumawe (Indonesia) and Pulau Pinang (Malaysia) from June 2009 to September 2010. The highest condition index (CI) value of A. granosa was recorded from Pulau Pinang and significantly different compared to Banda Aceh and Lhokseumawe. The gonadal index (GI) value of A. granosa from Banda Aceh (r = 0.469, P > 0.05) and Pulau Pinang (r = 0.123, P > 0.05) did not show any correlation to their condition index, whereas gonadal index of A. granosa from Lhokseumawe (r = 0.609, P < 0.05) showed a moderate positive correlation to the condition index values.